Peripheral neuropathy in patients in haemodialysis treatment - Santos, Adriana Ondina Pestana (2012)
Background: Chronic kidney disease is a worldwide public health problem. Its prevalence is 15% in developed countries. End-stage kidney disease is known to be associated with peripheral neuropathy, which is classically a distal symmetrical length-dependent, sensorimotor polyneuropathy. Diagnosis of peripheral neuropathy is complex. For its early detection and appropriate intervention, it is required careful clinical assessment with history and physical examination including neurological examination, laboratory testing and electrodiagnostic studies or nerve biopsy, if the diagnosis remains unclear. Objectives: To evaluate the electrophysiological changes in a subgroup of patients with end-stage kidney disease treated with haemodialysis and correlate them with the clinical course of the disease. Methods: Twenty seven patients with end-stage kidney disease in haemodialysis maintenance treatment from the dialysis unit of Amato Lusitano Hospital’s were submitted to electrophysiological evaluation from October 2011 to January 2012 in the Faculty of health Sciences of the University of Beira Interior. As inclusion criteria we considered the duration of haemodialysis treatment and the ability to do the exam. All patients with any disease that might give rise to peripheral neuropathy, except diabetes mellitus were excluded. Results: Peripheral neuropathy was observed in 92.6% of patients. We did not find any correlation with neurologic symptoms neither with haemodialysis duration, p=0.051. Diabetes did not increase the risk of peripheral neuropathy. Diabetic patients when compared with non-diabetic patients had 6.7 times the risk of having sensorimotor neuropathy. Diabetic patients alone had 3.094 times more risk to have sensorimotor neuropathy. Conclusions: Peripheral neuropathy seems to be a silent partner in the multifactorial pathology of this group of patients. The absence of clinical findings may delay the diagnosis of peripheral neuropathy. Thereafter a multidisciplinary approach for prevention, diagnosis and treatment of this type of complications is crucial.